Vanet : challenges and opportunities - Botkar, Sonali P. (Boca Raton, FL : CRC Press, 2021)
VANET (vehicular ad hoc network) is a subgroup of MANET (mobile ad hoc network). It enables communication among vehicles on the road and between related infrastructures. This book addresses the basic elements of VANET along with components involved in the communication with their functionalities and configurations. It contains numerous examples, case studies, technical descriptions, scenarios, procedures, algorithms, and protocols, and addresses the different services provided by VANET with the help of a scenario showing a network tackling an emergency. Features: Covers all important concepts of VANET for beginners and different road scenarios in VANET Covers essential communication protocols in VANET Introduces approaches for VANET implementation using simulators Provides a classification of messages and a priority-based message forwarding strategy This book is aimed at undergraduates, postgraduates, industry, researchers, and research scholars in information and communications technology.
OCLC-licensed vendor bibliographic record.
Keywords: Vehicular ad hoc networks (Computer networks); COMPUTERS / Computer Engineering